Scientific Opinion on Flavouring Group Evaluation 91, Revision 3 (FGE.91Rev3): consideration of aliphatic, aromatic and α, β‐unsaturated sulfides and thiols evaluated by JECFA (53rd, 61st, 68th and 76th meetings), structurally related to substances in FGE.08Rev5. (10th June 2020) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; et al.
Abstract: The EFSA Panel on Food Additives and Flavourings was requested to evaluate 49 flavouring substances assigned to the Flavouring Group Evaluation 91 (FGE.91), using the Procedure as outlined in the Commission Regulation (EC) No 1565/2000. Forty‐four substances have been considered in FGE.91 and its revisions (FGE.91Rev1 and FEG.91Rev2). With regard to the remaining five flavouring substances considered in this revision 3 of FGE.91: two ([FL‐no: 12.065 and 12.079]) have been cleared with respect to genotoxicity in FGE.201Rev2; two ([FL‐no: 12.169 and 12.241]) were originally allocated to FGE.74Rev4 and one ([FL‐no: 12.304]) to FGE.08Rev5. The Panel considered the flavouring substance [FL‐no: 12.169] representative for the tertiary monothiols [FL‐no: 12.038, 12.085, 12.137, 12.138, 12.145, 12.252, 12.259, 12.241 and 12.304]. The substances were evaluated through a stepwise approach that integrates information on the structure–activity relationships, intake from current uses, toxicological threshold of concern (TTC), and available data on metabolism and toxicity. The Panel concluded that none of these 49 substances gives rise to safety concerns at their levels of dietary intake, estimated on the basis of the 'Maximised Survey‐derived Daily Intake' (MSDI) approach. The specifications for the materials of commerce have also been considered and found adequate for all 49 flavouring substances. For five substances [FL‐no: 12.077, 12.162, 12.265, 12.267 and 17.036], evaluated through the Procedure in FGE.91Rev2, no normal and maximum use levels are available. For 10 substances [FL‐no: 12.065, 12.038, 12.079, 12.108, 12.139, 12.264, 12.274, 12.252, 12.284 and 12.304], the modified Theoretical Added Maximum Daily Intake (mTAMDI) intake estimates are above the TTC for their structural class. Therefore, for these 15 substances, more detailed data on uses and use levels should be provided in order to refine their exposure assessments and to finalise their safety evaluations.